The Effect of Supervision on Product Quality with Employee Competence as A Moderating Variable in The Garment Industry Of The Sewing Department in West Java - Imbrani, Hari; Setiawan, Iwan; Irfansyah, Zenith (UPT Publikasi Ilmiah UNISBA, 2025)
Based on the results of a pre-survey conducted by researchers in the garment industry at the Sewing Department in West Java, it is indicated that the production process has not fully run well, there are still several problems such as processes that are still not in accordance with standard operating procedures, there are still employees who lack focus, and there are still products that are not in accordance with the standards that pass the finishing section. The population in this study was 271. The technique used in determining the sample is using the solvin formula so that the sample results total 73 sample. The analysis used is linear regression, correlation, coefficient of determination, and hypothesis testing with the t test. Based on the results of the correlation test value obtained, it has a coefficient correlation is 0.367 can be concluded the between supervision and product quality with employee competence as a moderating variable the level relationship is low. The results obtained from the linear regesion analysis of the value of Y = 43.601+0.003X which means that every addition to the supervisory value moderated by employee competence, the product quality value will increase by 0.003. For hypothesis testing used in this study is to use a two-way t test. The hypothesis test using the t test obtained a calculated t value of 3.321 and t table determined is 1.993, accepted which means that supervision has an influence on product quality with employee competence as a variable moderating.